2020
DOI: 10.1186/s12916-020-01724-5
|View full text |Cite
|
Sign up to set email alerts
|

Antibody responses to a suite of novel serological markers for malaria surveillance demonstrate strong correlation with clinical and parasitological infection across seasons and transmission settings in The Gambia

Abstract: Background As malaria transmission declines, sensitive diagnostics are needed to evaluate interventions and monitor transmission. Serological assays measuring malaria antibody responses offer a cost-effective detection method to supplement existing surveillance tools. Methods A prospective cohort study was conducted from 2013 to 2015 in 12 villages across five administrative regions in The Gambia. Serological analysis included sample… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 50 publications
4
30
0
Order By: Relevance
“…Despite the lack of a clearly defined relationship between antigen-matched targets from opposing expression systems, we remain confident that microarrays utilising IVTT or purified recombinant proteins are able to produce compelling and biologically relevant data. Indeed, our data show age-dependent trends in antibody responses (typical of highly endemic populations [1][2][3]) irrespective of expression system (Supplementary figure 2), lending weight to the applicability of either methodology in serological assays [33][34][35][36][37][38][39][40][41][42][43][44][45][46].…”
Section: Ama1 -Ivtt_1mentioning
confidence: 55%
“…Despite the lack of a clearly defined relationship between antigen-matched targets from opposing expression systems, we remain confident that microarrays utilising IVTT or purified recombinant proteins are able to produce compelling and biologically relevant data. Indeed, our data show age-dependent trends in antibody responses (typical of highly endemic populations [1][2][3]) irrespective of expression system (Supplementary figure 2), lending weight to the applicability of either methodology in serological assays [33][34][35][36][37][38][39][40][41][42][43][44][45][46].…”
Section: Ama1 -Ivtt_1mentioning
confidence: 55%
“…A subset of eight antigens (Etramp5.Ag1, GEXP18, HSP40.Ag1, Rh2.2030, EBA175, Pf MSP1 19 , Pf AMA1, Pf GLURP.R2) were selected from an initial screen of 856 candidates on an in vitro transcription and translation (IVTT) protein microarray based on their correlation with clinical and parasitological endpoints in previous studies. 12 , 22 Antigens were expressed in Escherichia coli ( E.coli ) as glutathione S-transferase (GST)-tagged fusion proteins, except for Pf AMA1 expressed in Pichia pastoris as a histidine-tagged protein. Non-malaria reactivity against GST-tagged fusion proteins were assessed using IgG responses to GST-coupled beads, and samples with greater than 1000 median fluorescence intensity (MFI) were excluded from analyses due to high non-specific IgG response.…”
Section: Methodsmentioning
confidence: 99%
“…Serological methods are increasingly being used alongside clinical and parasitological metrics for surveillance. Studies in moderate to low transmission regions across sub-Saharan Africa, including Tanzania, 9 Equatorial Guinea, 10 South Africa 11 and The Gambia, 12 have found that malaria-specific antibody responses are highly correlated with parasitological endpoints. Serological assays can be a particularly useful tool in settings where parasite densities commonly fall below the detection limit of other diagnostics such as microscopy or RDTs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations